2018
DOI: 10.1007/s12094-018-1872-x
|View full text |Cite
|
Sign up to set email alerts
|

Are endometrial cancer radiotherapy results age related?

Abstract: Patients ≥ 65 years had a worse outcome in comparison to younger patients. Late vaginal, rectal and bladder toxicities were similar in the three groups, although an increase of severe late small bowel toxicity led to IMRT in patients ≥ 80 years. Further larger studies are needed including quality of life analysis in patients ≥ 80 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…A course of curative radiotherapy may last for six to eight weeks and may potentially affect an older patient’s quality of life (QOL) because of their limited mobility [11,12]. Those issues need to be addressed to provide potential solutions which may improve quality of care for older cancer patients, such as hypofractionated and stereotactic body radiation [6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A course of curative radiotherapy may last for six to eight weeks and may potentially affect an older patient’s quality of life (QOL) because of their limited mobility [11,12]. Those issues need to be addressed to provide potential solutions which may improve quality of care for older cancer patients, such as hypofractionated and stereotactic body radiation [6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy is most commonly used as adjuvant therapy for intermediate- to high-risk carcinomas. 45 Chemotherapy is used as postoperative treatment for high-risk stage I and II disease, stage III and IV disease or as primary treatment for unresectable advanced, metastatic, or recurrent disease. 5 The combination of carboplatin and paclitaxel is considered first- line chemotherapy.…”
Section: Adjuvant Treatmentmentioning
confidence: 99%
“…Endometrial cancer is the most common gynecologic cancer, and it is frequently diagnosed in elderly patients 1. Nearly two-thirds of patients with endometrial cancer in developed countries are over 65 years old at the time of diagnosis, and the incidence is rising as life expectancy increases worldwide 2 3. Several studies have shown that older age is an indicator of a poor prognosis in patients with endometrial cancer 4 5.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy is well tolerated by elderly patients with endometrial cancer, with more than 90% of patients completing their treatments 11 12. However, the treatment and toxicity outcomes of elder patients with endometrial cancer treated with adjuvant radiotherapy has been rarely evaluated 3 13. A few reports have described an increase in radiotherapy complications, while others have indicated that the incidence of complications among older populations is comparable to that of younger populations 3 13…”
Section: Introductionmentioning
confidence: 99%